سر سید کی قرآنیات سے متعلق کاوشوں میں مسیحی مسلم مباحث: Sir Syed’s Contributions to Quranic Studies: A Focus on Christian-Muslim Discourse - Akram, Samreen; Ahmad Qadri, Dr. Hafiz Khurshid (Al-Amīr Research Journal for Islamic Studies, 2024)
This study delves into Syed Ahmad Khan’s contributions to Quranic studies, with a particular focus on his discourse on Christianity. Syed Ahmad Khan, a prominent figure in the subcontinent, made significant efforts in various fields, including politics, society, economics, culture, and religion. His religious contributions are diverse, encompassing modern theology, beliefs, and interfaith dialogues. This research specifically examines his works related to the study of religions, particularly Christianity, within the Quranic context. Syed Ahmad Khan’s writings such as "Ahkam Ta’am Ahl al-Kitab" and "Tafsir al-Quran wa Huwa al-Huda wal-Furqan" provide a detailed analysis of Christian theological debates in light of the Quran. The paper aims to explore these discussions and their implications on Muslim-Christian relations, shedding light on Syed Ahmad Khan’s methodological approach and his efforts to clarify misconceptions regarding the permissibility of consuming food prepared by Christians. Keywords: Syed Ahmad Khan, Quranic Studies, Christianity, Interfaith Dialogue, Muslim-Christian Relations.